Microbiological blood profile among COVID-19 patients hospitalized in a tertiary care hospital: An observational study - Meena, Mamta; Priyanka Singh,; Mittal, Arvind Kumar; Deepti Chaurasia, (Asian Journal of Medical Sciences, 2023)
Background: Bacterial coinfection contributes to increase morbidity and morbidity of viral respiratory infections and may lead to fatal outcome during its course of illness. Aims and Objectives: The main objective of this study was to determine the bacteriological profile of COVID-19 patients admitted in hospital, their antibiotic susceptibility, and their association with severity. Materials and Methods: The present study was retrospective observational cross-sectional study of all patients admitted for COVID-19 at Gandhi Medical College and Hamidia Hospital, Bhopal (MP) between (March 2020 and December 2020). Demographic, comorbid conditions, and microbiological data were compared HBD and intensive care unit (ICU) admissions and role secondary coinfection in severity and mortality. Results: Thirty percentages of percent of patients showed bacterial growth, Staphylococcus aureus was most common, followed by Pseudomonas aeruginosa. Mean±SD of age was 43.6±21.6. Antibiotic resistance of cefoxitin, cotrimoxazole, and azithromycin was seen in maximum Gram-positive growth, whereas sensitivity for linezolid and gentamicin was present in 10–16% cases. Highest antibiotic resistance in Gram-negative growth was seen for ceftozidime, amikacin, imipenem, and meropenem, whereas sensitivity of colistin antibiotic was highest in Gram-negative growth. Conclusion: Coinfection rates increase in patients admitted to the ICU, despite frequent prescription of broad-spectrum antibiotics. Infectious diseases practitioners carry the burden of life-saving and provide for societal trust that is effective antibiotic therapy in the face of these changes. With a growing body of evidence supporting short-course, antimicrobial therapy “Shorter Is Better” should be the new mantra.